2021
DOI: 10.3892/or.2021.8155
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotanshinone exerts antitumor effects and improves the effects of cisplatin in anaplastic thyroid cancer cells

Abstract: Anaplastic thyroid cancer (ATC) is the most aggressive type of thyroid cancer and is responsible for 20-50% of thyroid cancer-associated deaths. The absence of response to conventional treatments makes the search for novel therapeutics a clinical challenge. In the present study, the effects of 15,16-dihydrotanshinone I (DHT), a tanshinone extracted from Salvia miltiorrhiza Bunge (Danshen), which has previously been shown to possess anticancer activity, were examined in two human ATC cell lines. DHT significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
1
5
0
Order By: Relevance
“…Lee et al demonstrated that DHT treatment induces a decrease in cell population in the Gl phase, an increase in the S phase cells and apoptosis in erythroleukemia cells resistant to Adriamycin [ 44 ]. These results are consistent with those we observed in ATC cells treated with DHT [ 27 ], suggesting a similar mechanism underlying the effects observed in ATC-PTX cells.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Lee et al demonstrated that DHT treatment induces a decrease in cell population in the Gl phase, an increase in the S phase cells and apoptosis in erythroleukemia cells resistant to Adriamycin [ 44 ]. These results are consistent with those we observed in ATC cells treated with DHT [ 27 ], suggesting a similar mechanism underlying the effects observed in ATC-PTX cells.…”
Section: Discussionsupporting
confidence: 93%
“…In particular, we demonstrated that DHT, a lipophilic abietane diterpene compound extracted from the dried root of Salvia miltiorrhiza , has an antitumor action in ATC cell lines, and this action is in part mediated by the regulation of the HuR-MAD2 axis known to be involved in the proliferation, survival and aggressiveness of this tumor [ 42 , 43 ]. In this study, we evaluated the effects of DHT on ATC cell lines resistant to Paclitaxel and found that DHT was effective in reducing cell viability in SW1736-PTX and 8505C-PTX cells with an EC50 absolutely comparable with that observed in non-resistant ATC cells in our previous work [ 27 ]. Lee et al demonstrated that DHT treatment induces a decrease in cell population in the Gl phase, an increase in the S phase cells and apoptosis in erythroleukemia cells resistant to Adriamycin [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its dismal prognosis, it is responsible for 40–50% of total thyroid cancer-related deaths [ 30 ]. In recent years, research has produced great efforts in an attempt to find an effective treatment against ATC, such as the use of taxane, dabrafenib, or trametinib (in patients harboring the BRAF p.V600E mutation) [ 31 ]; natural compounds such as DHT [ 32 ]; or molecules that can alter epigenetic pathways [ 33 ]. However, there is still no standardized and effective treatment for this type of malignancy, partly because ATC cells are able to evade most therapeutic strategies by developing chemoresistance [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dihydrotanshinone I (DHT) is a natural compound extracted from Danshen. According to the reports, DHT has antitumor ( Allegri et al, 2021 ), anti-inflammatory ( Wang et al, 2020 ), and immunomodulatory effects ( Wang et al, 2020 ). Evidence has emerged that DHT attenuates crystalline silica–induced lung inflammation by regulating the immune response and inhibiting STAT1/STAT3 ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%